Knee osteoarthritis related pain: a narrative review of diagnosis and treatment - Alshami, Ali Muteb (International Journal of Health Sciences, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--> Background: Osteoarthritis is a common progressive joint disease, involving not only the joint lining but also cartilage, ligaments, and bone. For the last ten years, majority of published review articles were not specific to osteoarthritis of the knee, and strength of evidence and clinical guidelines were not appropriately summarized. Objectives: To appraise the literature by summarizing the findings of current evidence and clinical guidelines on the diagnosis and treatment of knee osteoarthritis pain. Methodology: English journal articles that focused on knee osteoarthritis related pain were searched via PubMed (1 January 2002 – 26 August 2012) and Physiotherapy Evidence Database (PEDro) databases, using the terms 'knee', 'osteoarthritis' and 'pain'. In addition, reference lists from identified articles and related book chapters were included as comprehensive overviews. Results: For knee osteoarthritis, the highest diagnostic accuracy can be achieved by presence of pain and five or more clinical or laboratory criteria plus osteophytes. Some inconsistencies in the recommendations and findings were found between the clinical guidelines and systematic reviews. Generally, paracetamol, oral and topical non-steroidal anti-inflammatory drugs, opioids, corticosteroid injections and physical therapy techniques, such as therapeutic exercises, joint manual therapy and transcutaneous electrical nerve stimulation, can help reduce pain and improve function. Patient education programs and weight reduction for overweight patients are important to be considered. Conclusions: Some inconsistencies in the recommendations and findings were found between the clinical guidelines and systematic reviews. However, it is likely that a combination of pharmacological and non-pharmacological treatments is most effective in treating patients with knee osteoarthritis. Keywords Arthritis, Guidelines, Humans, Physiotherapy, Review <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->